DETERMINASI KUALITAS AUDIT: PERAN KOMITE AUDIT SEBAGAI MODERASI - Budiantoro, Harry; Santosa, Perdana Wahyu; Challen, Auliffi Ermian; Primadini, Adinda; Tantri Ningsih, Hestin Agus (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2025)
This study aims to examine the effect of audit tenure, audit rotation, Public Accounting Firm (KAP) size, and audit fees on audit quality, with the audit committee as a moderating variable in companies included in the SRI-KEHATI index for the 2019–2023 period. The phenomenon of differences in previous research results regarding the effectiveness of auditor rotation and the role of corporate governance forms the basis of this study. The data used is secondary data from the annual reports and financial statements of companies included in the SRI-KEHATI index. The analysis was conducted using SPSS version 31 software using logistic regression. The results show that KAP size and audit fees have a significant effect on audit quality, while audit rotation has no significant effect, and audit tenure shows a varying effect. In addition, the audit committee is unable to moderate the relationship between audit tenure and KAP size with audit quality. These findings confirm that audit quality is more influenced by KAP reputation and audit fees than simply auditor turnover. This study concludes that companies need to be more selective in choosing KAPs and strengthen the role of audit committees. Managerial implications: The results of this study can be used as strategic considerations by management, regulators, and investors in improving governance and maintaining sustainable company audit quality